Diffusion tensor imaging and related techniques in tuberous sclerosis complex: review and future directions. (September 2013) - Peters, Jurriaan M; Taquet, Maxime; Prohl, Anna K; Scherrer, Benoit; van Eeghen, Agnies M; Prabhu, Sanjay P; Sahin, Mustafa; Warfield, Simon K
In this article, the authors aim to introduce the nonradiologist to diffusion tensor imaging (DTI) and its applications to both clinical and research aspects of tuberous sclerosis complex. Tuberous sclerosis complex is a genetic neurocutaneous syndrome with variable and unpredictable neurological comorbidity that includes refractory epilepsy, intellectual disability, behavioral abnormalities and autism spectrum disorder. DTI is a method for modeling water diffusion in tissue and can noninvasively characterize microstructural properties of the brain. In tuberous sclerosis complex, DTI measures reflect well-known pathological changes. Clinically, DTI can assist with detecting the epileptogenic tuber. For research, DTI has a putative role in identifying potential disease biomarkers, as DTI abnormalities of the white matter are associated with neurocognitive morbidity including autism. If indeed DTI changes parallel phenotypical changes related to the investigational treatment of epilepsy, cognition and behavior with mTOR inhibitors, it will facilitate future clinical trials.